Early Settlers and Their Places in the Tandilia Range (Pampean region, Argentina) - Mazzia, Natalia Irene (2012)
A microregional approach has been applied to studies on the early peopling of the Lobería ranges, in the central east portion of Tandilia, in the Pampean Region, Argentina. Over the years several sites in different placements have been excavated and sources for raw materials have been identified.Recent research has focused on specific aspects, in this paper we shall address one of these issues based on landscape archaeology. We apply the concept of place as a point of departure to deal with the complexities of hunter gatherer landscape. Thus, different places are briefly described and their topographic setting is reassessed based on recent anthropological research.